Long‐term oncological outcomes of patients with paratesticular sarcoma. (6th May 2019) - Goldberg, Hanan; Wong, Lih‐Ming; Dickson, Brendan; Catton, Charles; Yap, Stanley A.; Alkasab, Thamir; Evans, Andrew; van der Kwast, Theodorus; Jewett, Michael A. S.; Hamilton, Robert J.
Abstract : Objectives: To present long‐term oncological outcomes of patients with paratesticular sarcoma treated by a multidisciplinary team. Patients and methods: Patients managed at the Princess Margaret Cancer Centre, between 1990 and 2012, were analysed. A sarcoma expert performed central pathology review. Kaplan–Meier graphs compared local recurrence (LR), metastasis, and overall survival (OS) of patients treated with hemiscrotectomy vs those who did not. Univariable Cox proportional hazards analysis was performed to delineate predictors of LR, metastasis, and OS. Results: Overall, 51 patients with a median (interquartile range) follow‐up of 132 (51.6–226.8) months were analysed. At presentation, 92.2% (47 patients) had localised disease. Only five patients (9.8%) had undergone initially planned hemiscrotectomy. Completion and salvage hemiscrotectomy was performed in 25 (54.3%) and seven (15.2%) patients, respectively. Recurrence and metastasis occurred in 12 (25.5%) and 10 patients (19.6%), respectively. At the last follow‐up, 21.6% (11 patients) had died, with eight dying from their disease. Kaplan–Meyer graphs demonstrated that hemiscrotectomy improved LR (median not reached vs 62.4 months, log‐rank P  = 0.008) and OS (median not reached vs 168 months, log‐rank P  = 0.081). Univariable analysis found hemiscrotectomy to be associated with a lower LR rate (hazard ratio [HR] 0.21, P  = 0.02), whilst positive margins at initial surgery were associated with increased LR (HR 4.81, P  = 0.047). No metastasis predictors were found, but age (HR 1.04, 95% confidence interval [CI] 1.0–1.08; P  = 0.02) and non‐localised disease at presentation (HR5.17, 95% CI 1.33–20.06; P  = 0.017) were associated with worse OS. Conclusion: Paratesticular sarcoma is a rare tumour, predominantly manifesting as localised disease. Most patients receive an initial suboptimal oncological surgery. Improved long‐term outcomes are demonstrated following early hemiscrotectomy.